Innovation of Digital Periodontal Probe Based on Camera Sensor as Automation for Identification of Gingival Discoloration and Anterior Gingival Recession - Rike Widayanti; Supriyana Supriyana; Diyah Fatmasari (Journal of Community Health Provision, 2026)
Periodontal disease remains a major oral health problem. This study aimed to develop and conduct a preliminary evaluation of a camera sensor-based digital periodontal probe for detecting gingival discoloration and gingival recession. The study employed a Research and Development (R&D) approach followed by a paired comparative assessment between manual and digital examination methods on the same subjects. The study involved 30 patients and 30 dental health professionals. Product feasibility was evaluated through expert validation using Aiken’s V, while reliability was assessed using the Intraclass Correlation Coefficient (ICC). Differences between manual and digital examination methods were analyzed using the Wilcoxon Signed Rank Test. The results showed no statistically significant difference in gingival discoloration detection between manual and digital methods (p=0.251). In contrast, a statistically significant difference was observed in gingival recession classification outcomes (p=0.011). The digital method identified more moderate and severe recession cases; however, this finding reflects differences in classification outcomes and does not necessarily indicate superior diagnostic performance. Expert validation indicated high content validity (Aiken’s V=0.897) and acceptable reliability (ICC=0.796). This study suggests that the developed tool has potential for use in periodontal screening and digital documentation. Further studies with larger sample sizes, reference standards, and agreement analysis are required to confirm the diagnostic accuracy and broader clinical applicability of the device.